1987
DOI: 10.1161/01.cir.75.4.768
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients with the antibiotic-sterilized aortic homograft valve inserted freehand in the aortic position.

Abstract: A series of 252 isolated aortic homograft valves in 248 patients have been followed for 9 to 16.5 years (mean 10.8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(46 citation statements)
references
References 31 publications
0
44
0
2
Order By: Relevance
“…4 Homograft valves are used in the aortic position and do not require long-term anticoagulation. 14 There is limited informa-tion on the survival and valve complications of young women with homografts and no information on the effect of pregnancy on valve survival. 15,16 In this study, we investigated which type of valve replacement (mechanical, bioprosthetic, or homograft) was associated with the greatest long-term survival in young women and compared the rate of valve complications with each valve type.…”
Section: See P 2613mentioning
confidence: 99%
“…4 Homograft valves are used in the aortic position and do not require long-term anticoagulation. 14 There is limited informa-tion on the survival and valve complications of young women with homografts and no information on the effect of pregnancy on valve survival. 15,16 In this study, we investigated which type of valve replacement (mechanical, bioprosthetic, or homograft) was associated with the greatest long-term survival in young women and compared the rate of valve complications with each valve type.…”
Section: See P 2613mentioning
confidence: 99%
“…4,5 Preservation methods included chemical preservation, irradiation, and freeze drying but resulted in an unacceptable incidence of structural deterioration. 6 Improved results were then obtained with antibiotic sterilization 7 and cryopreservation. Many centers now use cryopreserved heart valves based on work by O'Brien et al 8 However, significant controversy remains regarding valve preservation, because the effects of the various preservation techniques on allografts have not been clearly defined.…”
mentioning
confidence: 99%
“…Our results are also in agreement with previously published data that showed that AAV primary degeneration rapidly accelerates 10 years after the operation when using the subcoronary approach. 7,11,28 Although our study suggests that in the root replacement technique AAV dysfunction does not accelerate after this time period, a follow-up of Ͼ15 years is required to strengthen our findings. In addition, we have shown that there is a different echocardiographic pattern of AAV degeneration in different types of surgical valve replacement procedures.…”
Section: Resultsmentioning
confidence: 57%
“…6 -10 However, like other tissue valves, AAV durability is still suboptimal. [11][12][13] AAV degeneration usually accelerates 10 to 15 years after implantation, making a reoperation a likely scenario for younger patients. 7 The causes of AAV degeneration are under intense investigation, but they seem to be complex and multifactorial.…”
mentioning
confidence: 99%